2013
DOI: 10.1111/pops.12015
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy Accounts as Intergroup Theories: Challenging Dominant Understandings of Social Power and Political Legitimacy

Abstract: Conspiracy accounting is often regarded as an atypical, pathological form of political reasoning, and little research has considered how ordinary social actors may refer to political conspiracies in the course of argument. In this article, we consider the spontaneous use of conspiracy narratives by politically engaged Greek citizens in interview discussions of the Macedonian crisis. Analysis revealed that conspiracy narratives were typically used to challenge dominant representations that attributed the Macedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 109 publications
3
54
0
15
Order By: Relevance
“…This definition implies that at a group level, belief in a conspiracy theory signifies a categorization of the powerless in-group as the believer of the conspiracy theory and a powerful out-group as the perpetrator (Kofta, 1995;Sapountzis & Condor, 2013). Indeed, some studies (e.g., Abalakina-Paap, Stephan, Craig, & Gregory, 1999;Crocker, Luhtanen, Broadnax, & Blaine, 1999) have observed that the more individuals feel powerless the more they believe in a theory that certain events are created by a conspiracy of powerful agents.…”
Section: Belief In a Conspiracy Theory Due To A Sense Of Victimhoodmentioning
confidence: 95%
“…This definition implies that at a group level, belief in a conspiracy theory signifies a categorization of the powerless in-group as the believer of the conspiracy theory and a powerful out-group as the perpetrator (Kofta, 1995;Sapountzis & Condor, 2013). Indeed, some studies (e.g., Abalakina-Paap, Stephan, Craig, & Gregory, 1999;Crocker, Luhtanen, Broadnax, & Blaine, 1999) have observed that the more individuals feel powerless the more they believe in a theory that certain events are created by a conspiracy of powerful agents.…”
Section: Belief In a Conspiracy Theory Due To A Sense Of Victimhoodmentioning
confidence: 95%
“…By portraying a disliked outgroup as a sinister enemy of ambiguously vast power, conspiracy theories may help to manage threat and anxiety (Kofta and Sędek, 2005; Swami, 2012; Grzesiak-Feldman, 2013; Sullivan et al, 2014; Mashuri and Zaduqisti, 2015). Finally, theoretical and qualitative works present a convincing case that conspiracy theorizing is very often an anti-authoritarian activity, focused on challenging dominant societal power structures and providing counter-narratives to mainstream understandings of the world (Raab et al, 2013; Sapountzis and Condor, 2013; Harambam and Aupers, 2015). …”
Section: Other Conspiracy Theoriesmentioning
confidence: 99%
“…The content of conspiracy beliefs is specific, in the form of framing an out-group as a dangerous, powerful, or deceptive adversary (Kofta, 1995). As contended by Sapountzis and Condor (2013), belief in conspiracy theories signifies a dualistic account of intergroup relations with which members of the ingroup are apt to ascribe any events to a direct design on the part of a powerful out-group. In support of this notion, Imhoff and Bruder (2014) recently reported that participants' belief in conspiracy theories related to their negative stereotyping against powerful outgroups regarded as less likable and more threatening.…”
Section: Introductionmentioning
confidence: 99%